Livestock Extension and Technology Transfer - Chander, Mahesh; Tripathi, Hema (Indian Farming, 2015)
Human resource has been a major constraint over the years, but the existing faculty of Division of Extension Education at IVRI is performing well through different entities. Extension Education, ATIC, KVK and Communication centre. Further, there is also a need for effective collaboration among different stakeholders for effective generation and transfer of technologies to serve the farming communities on a large scale.